Autologous Mesenchymal Stem Cells, Applied in a Bioabsorbable Matrix, for Treatment of Perianal Fistulas in Patients With Crohn's Disease - Dietz, Allan B; Dozois, Eric J; Fletcher, Joel G; Butler, Greg W; Radel, Darcie; Lightner, Amy L; Dave, Maneesh; Friton, Jessica; Nair, Asha; Camilleri, Emily T; Dudakovic, Amel; van Wijnen, Andre J; et al. (Gastroenterology (New York, N.Y. 1943), 2017)
In patients with Crohn's disease, perianal fistulas recur frequently, causing substantial morbidity. We performed a 12-patient, 6-month, phase 1 trial to determine whether autologous mesenchymal stem cells, applied in a bioabsorbable matrix, can heal the fistula. Fistula repair was not associated with any serious adverse events related to mesenchymal stem cells or plug placement. At 6 months, 10 of 12 patients (83%) had complete clinical healing and radiographic markers of response. We found placement of mesenchymal stem cell-coated matrix fistula plugs in 12 patients with chronic perianal fistulas to be safe and lead to clinical healing and radiographic response in 10 patients. ClinicalTrials.gov Identifier: NCT01915927.